Active anycast server selection / Noor Suhaini Mila Suparman - Suparman, Noor Suhaini Mila (2008)
The proposed active anycast server selection is a network supported server selection method which can be used in replicated server environment. The replicated servers are scattered in the network and thus allow the distribution of access from clients geographically. To permit communication between client and server, each route must have an active router to ensure that it is capable in forwarding the packets efficiently. An active router is responsible to select and make decisions on the appropriate server to handle request based on server selection used. The work investigates three different active anycast server selection method; random, round robin and nearest server in terms of average server throughput and load balancing by means of simulation using J-Sim. It was found that, round robin server selection is selected to be the best server selection method for equal server bandwidth since the request from client is distributed equally between the servers while the random server selection is selected to be the best server selection method for different server bandwidth since average throughput for server h7 is lower than h5 which reflects the initial setting of bandwidth of server h7 lower than h5.